2014
DOI: 10.1515/hf-2014-0057
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and chemical composition of beech wood exposed for 30 and 120 days to white-rot fungi

Abstract: The effects of exposing specimens of Oriental beech [Fagus sylvatica subsp. orientalis (Lipsky) Greuter and Burdet] to the white-rot fungi Pleurotus ostreatus (Jacq.: Fr.) Kummer and Trametes versicolor (L.: Fr.) Pilát strain 325 have been studied concerning the mechanical properties and chemical composition in terms of carbohydrates, cellulose, and lignin. Biological decay tests were carried out in accordance with the EN 113 standard specifications for 30 and 120 days. P. ostreatus had nearly the same deterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 9 publications
2
29
0
1
Order By: Relevance
“…Several scientific studies have evaluated wood degradation by fungi causing decay damage to trees and wood, which causes the simultaneous degradation of lignin and cellulose (Goktas et al 2008(Goktas et al , 2010Olfat 2014). The white-rot fungi initially degrade lignin, followed by the carbohydrates; therefore, defibrillated materials remain through the dissolution of the middle lamella compounds (Eaton and Hale 1993;Schmidt 2006;Bari et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several scientific studies have evaluated wood degradation by fungi causing decay damage to trees and wood, which causes the simultaneous degradation of lignin and cellulose (Goktas et al 2008(Goktas et al , 2010Olfat 2014). The white-rot fungi initially degrade lignin, followed by the carbohydrates; therefore, defibrillated materials remain through the dissolution of the middle lamella compounds (Eaton and Hale 1993;Schmidt 2006;Bari et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…The highest weight loss in wood of F. orientalis occurs after 16 weeks of colonization by the wood-rotting Basidiomycetes, Coriolus versicolor (47.5%), in comparison with 10 weeks (13.2%) (Olfat 2014). Recent research in north-east Iran found that more than 90 percent of wood decay in standing and felled trees, including oriental beech (Fagus orientalis), is caused by white-rot fungi (Bari et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of the cell wall and its chemical composition as well as the different enzymatic mechanisms of rotting fungus, are directly associated with wood rotting (Schmidt 2006). This is indicative of the importance of this kind of correlation in the fungal deterioration process (Bari et al 2014). …”
Section: Weight Lossmentioning
confidence: 78%
“…However, for the extractive levels, correlation was lower. This may occur because wood undergoes a wide range of changes during rotting, causing changes in the chemical composition of the cell wall during exposure to fungus attack (Schmidt 2006, Maresi et al 2013, Bari et al 2014.…”
Section: Weight Lossmentioning
confidence: 99%